2013
DOI: 10.1095/biolreprod.112.101253
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Bicarbonate-Induced Radical Signaling in Oxysterol Formation and Sterol Depletion of Capacitating Mammalian Sperm During In Vitro Fertilization1

Abstract: This study demonstrates for the first time that porcine and mouse sperm incubated in capacitation media supplemented with bicarbonate produce oxysterols. The production is dependent on a reactive oxygen species (ROS) signaling pathway that is activated by bicarbonate and can be inhibited or blocked by addition of vitamin E or vitamin A or induced in absence of bicarbonate with pro-oxidants. The oxysterol formation was required to initiate albumin dependent depletion of 30% of the total free sterol and >50% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 46 publications
4
86
0
1
Order By: Relevance
“…Although media containing mbcd promoted high levels of heterologous ZP interaction, a recent study of murine and porcine sperm capacitation has suggested that the artificial depletion of sterols mediated by this agent may result in low IVF rayes (Boerke et al 2013). Such results purportedly stem from the dual action of this reagent in circumventing the bicarbonate-induced reactive oxygen species (ROS) oxysterol signalling pathway that leads to the removal of sperm surface sterols, in addition to its ability to induce oocyte degeneration in these species (Boerke et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although media containing mbcd promoted high levels of heterologous ZP interaction, a recent study of murine and porcine sperm capacitation has suggested that the artificial depletion of sterols mediated by this agent may result in low IVF rayes (Boerke et al 2013). Such results purportedly stem from the dual action of this reagent in circumventing the bicarbonate-induced reactive oxygen species (ROS) oxysterol signalling pathway that leads to the removal of sperm surface sterols, in addition to its ability to induce oocyte degeneration in these species (Boerke et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such results purportedly stem from the dual action of this reagent in circumventing the bicarbonate-induced reactive oxygen species (ROS) oxysterol signalling pathway that leads to the removal of sperm surface sterols, in addition to its ability to induce oocyte degeneration in these species (Boerke et al 2013). While the effect of mbcd on equine IVF rates and equine oocyte quality is yet to be examined, the very low concentration encountered by oocytes in our study is likely to limit any detrimental influence of this reagent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that ROS generation during capacitation may be necessary for cholesterol efflux from the sperm plasma membrane. ROS oxidizes cholesterol to form oxysterols; this appears to be associated with depletion of both oxysterols and unoxidized cholesterol from the plasma membrane (Brouwers et al 2011, Boerke et al 2013. It is postulated that formation of oxysterols may activate the sterol transporter proteins, which make sterols available to cholesterol acceptors such as albumin (Boerke et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the cholesterol complexing agent, methyl-b-cyclodextrin (MbCD), does not require cholesterol oxidation in order to effectively remove cholesterol from the sperm plasma membrane (Boerke et al 2013).…”
Section: Introductionmentioning
confidence: 99%